A first‐principles investigation on interactions between various surface‐terminated diamond films. (25th July 2019) - Jin, Xiuting; Liu, Fengbin; Si, Lina; Dou, Zhaoliang; Yan, Hongjuan; Li, Hong; Qu, Min
Abstract : To elucidate the influence of different terminations on diamond surface interaction, the geometry and electronic structures of the diamond films modified by different terminations (H, F, O, NH2, and OH) are studied by using the first principles method. Strong bonding is formed between the clean diamond surfaces, which suggest an obvious interface interaction. Both H and F terminals have significant effects on the reduction of the interface interactions. Due to the larger difference in electronegativity between C and F, the F termination layer has a higher electron density coverage to give a larger repulsive force. Therefore, the interaction between the F‐terminated diamond interfaces is stronger than that between the H‐terminated diamond interfaces. The O‐terminated diamond surfaces are unstable. The NH2 ‐ and OH‐terminals have weak interaction due to the presence of large functional group atoms that leads to an electronic offset.